Analysis of Land Rights Cancellation Process Due to Administrative Non-Compliance with Applicable Law in Indonesia: Analisis Proses Pembatalan Hak Atas Tanah Akibat Ketidaksesuaian Administrasi dalam Hukum yang Berlaku di Indonesia - Rendra Adi Wibowo; Bambang Eko Turisno (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Cancellation of land rights due to administrative discrepancies is a significant process in agrarian law in Indonesia. This study investigates the process of cancelling land rights based on applicable regulations, including the Basic Agrarian Law and relevant governmental regulations. Through an empirical legal approach, data were obtained from the analysis of legal documents. The results reveal the complexity of the cancellation process, the importance of legal certainty in land rights registration, and the necessity of transparency and fairness in handling land-related cases. This study contributes to understanding the implementation of agrarian law in practice and supports the improvement of regulations and the enhancement of land administration systems to increase the protection of community rights.